Essential thesaurus construction - Broughton, Vanda (Facet Pub., 2006)
This practical text examines the criteria relevant to the selection of a subject management system, describing the characteristics of some common types of subject tool, and taking the novice step-by-step through the process of creating a system for a specialist environment.